Post-Medium Literature? Two Examples of Contemporary Scandinavian - Bruhn Jørgen (Acta Universitatis Sapientiae: Philologica, 2013)
This article discusses two contemporary Scandinavian literary texts: Ursula Andkjaer Olsen’s Danish book of poetry called Havet er en scene [The Sea Is a Stage], and Abo Rasul’s (pseudonym for Matias Faldbakken) Norwegian novel Unfun. I intend to show that these texts exemplify two very different but nevertheless comparable positions in contemporary Scandinavian literature. Despite the differences, they resemble each other in that they actively mix medial constellations to offer social critique, and the aim of this article is thus to investigate the specific relation between medial mixture and social critique.